Nuclear energy - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2003)
This cd-rom discusses about nuclear energy, process the sun and other stars naturally occurs, the work of Marie, Pierre and Irene Curie, the process of fission which achieves an atomic explosion, and also the advantage of nuclear power
Teacher's guide in PDF and Microsoft Word format
System requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 Mb available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Nuclear energy -- Juvenile literature; Nuclear energy